THE DEMAND FOR CULTURAL SERVICES IN KOREA USING THE QUAIDS MODEL - Yoon, Suyoung; Heo, Shik (International Journal of Business and Society, 2017)
In order to investigate the demand for cultural services in Korea, we employ a QUAIDS model based on neoclassical microeconomic theory and estimate demand on cultural services, i.e., SR (Sports and Recreation), CEP (Cinema, Exhibition and Performing arts), and BC (Broadcasting and Content). We try to ascertain Korean households’ responsiveness to price and income changes as well as substitution and complementary relationships among cultural services. According to our results, the demands for cultural services in Korean households were more sensitive to price than income. Furthermore, our results showed that SR and CEP are a mutually complementary, while both SR and CEP are substitutes for BC. More specifically, this study is extended to the demand for cultural services by households’ characteristics. We found that main customers in CEP are female, while and those in SR are male. Additionally, both SR and CEP customers have higher incomes and price elasticity in older households, but opposite is true in households with higher education levels. Finally, BC has higher income elasticity in households over the age of 50 than other age groups. Our results may expect to provide some insight into government organizations to promote the arts and culture sector. Keywords: Cultural Services; QUAIDS Model, Income and Price Elasticities, Complementary and Substitutes, Korea.